Family businesses and community development: the role of small business owners and entrepreneurs. Issue 4 (8th July 2016) - Fitzgerald, Margaret A.; Muske, Glenn
Abstract: Family businesses contribute to the economies and social fabric of their communities, often forming the stable business core. Although identified as family businesses, they may also be classified as entrepreneurial or small businesses. Few empirical studies have validated the classification of either group – entrepreneur or small business – based on unique differences or contributions to economic development over time. In this study, panel data from three waves of the National Family Business Survey (USA) spanning 10 years were used to verify the distinct differences between groups. Results indicate the importance of supporting family business owners, whether entrepreneurs or small business owners, in economic development because each group makes important contributions to the long-term sustainability of its community's economic sector. While entrepreneurs achieve greater gross income and number of employees, small business owners offer stability during economic downturns. Suggestions to guide policy-makers and support agencies are offered.